La ciudad restauradora - Villalpando-Flores, Arturo Eduardo; Bustos-Aguayo, José Marcos (Pontificia Universidad Católica del Perú, 2024)
The symbiotic relationship between human beings and the environment has evolved in parallel, leaving its mark on the genetic structure of our species and the formulation of social statutes. This convergence is evident in the dynamics of modern life, the functional aspects, and the emotional anchors. Based on the postulates of environmental psychology and design proposals, this article presents a model called “restorative urbanism”, stating that proximity to urban nature is a critical element in the composition and design of urban environments, fostering better perceptions of external habitability and improving individual and collective well-being in biopsychosocial terms through the environmental restoration process, achieving urban-environmental and psychological sustainability. The importance of the proposal lies in its ability to question how the morphological characteristics of the sociophysical space influence the quality of the socioenvironmental, physical, and emotional relationships with the surrounding environment, especially in the face of urban, environmental, and climatic contingencies.

La relación simbiótica entre los seres humanos y el medio ambiente ha evolucionado paralelamente, dejando su huella en la estructura genética de nuestra especie y en la formulación de estatutos sociales. Esta convergencia es evidente en la dinámica de la vida moderna, los aspectos funcionales y los anclajes emocionales. Basándose en los postulados de la psicología ambiental y las propuestas de diseño, este artículo presenta un modelo denominado «urbanismo restaurador», afirmando que la proximidad a la naturaleza urbana es un elemento crítico en la composición y el diseño de los entornos urbanos, fomentando mejores percepciones de habitabilidad externa y mejorando el bienestar individual y colectivo en términos biopsicosociales a través del proceso de restauración ambiental, alcanzando una sostenibilidad urbano-ambiental y psicológica. La importancia de la propuesta radica en su capacidad para cuestionar cómo las características morfológicas del espacio sociofísico influyen en la calidad de las relaciones socioambientales, físicas y emocionales con el entorno circundante, especialmente ante las contingencias urbanas, ambientales y climáticas.
The Restorative City
Keywords: Urban environments; Biophilia; External habitability; Environmental restoration; Biopsychosocial well-being; Entornos urbanos; Biofília; Habitabilidad externa; Restauración ambiental; Bienestar biopsicosocial; https://purl.org/pe-repo/ocde/ford#5.04.00